Postfire Seismic Performance Of Reinforced Precast Concrete Columns - Demir, Ugur; Green, Mark F.; Ilki, Alper (Aperta, 2020)
Quantifying the seismic resistance of reinforced concrete buildings after fire is difficult because of the lack of information regarding their strength and ductility under earthquake loads. In this study, four full-scale flexure-controlled reinforced precast concrete columns were subjected to quasi-static reversed cyclic lateral loading under constant axial load to examine the seismic response of reinforced precast. concrete columns damaged by 30, 60, and 90 minutes of fire. For the first time, the impact of fire damage on force-displacement behavior, moment-curvature relationship, stiffness, energy dissipation capacity, and residual displacements was investigated through posttire seismic tests. Test results clearly indicated that the fire exposure did not. significantly affect the lateral-load-bearing capacity, failure modes, and ductility of the columns, with the exception of the specimen subjected to 90 minutes of tire exposure. The analytical study consisting of thermal and fiber-based structural analysis demonstrated that conventional principles of structural mechanics are valid for estimation of the postfire seismic behavior of reinforced precast concrete columns when the deteriorations in materials are realistically taken into account and the given algorithm is followed.